Profesionalisme Guru dalam Menumbuhkan Nilai Karakter Siswa Berbasis Nilai-Nilai Budaya 5S (Senyum, Sapa, Salam, Sopan, Santun) di SMK 1 Muhammadiyah Kasihan Bantul Yogyakarta - Sutarman; Yusutria (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The cultivation of 5S culture in instilling religious character imbues the teachings of Islamic values. So that professional teachers help grow the character values ​​of students who are still lacking and need to be instilled in order to get used to and have religious characters that are in accordance with Islamic teachings and national education goals. The aim is to determine the professionalism of teachers in growing religious character based on 5S culture. This research is quantitative with a population of 45 students in class XI SMK 1 Muhammadiyah Bantul Yogyakarta. Collecting information using questionnaires and documentation. The results of the research on the results of the growth of character values ​​are 100% teachers provide socialization and role models, 80% warmly welcome students, 100% teachers say hello, 90% give advice if there are mistakes, 100% teachers give awards to students who apply S5, 100% teachers are careful in speaking, 80% of teachers apply S5, 100% of teachers establish good cultural relations with parents and the community.